Contrasting life cycles of Southern Ocean pteropods alter their vulnerability to climate change - Gardner, Jessie; Peck, Victoria L.; Bakker, Dorothee C. E.; Tarling, Geraint A.; Manno, Clara (Frontiers in Marine Science, 2023)
Pteropods are a key part of biogeochemical cycling and epipelagic food webs in the Southern Ocean. However, shelled pteropods are vulnerable to climate change, due to their aragonite shells being particularly sensitive to ocean acidification. Currently our understanding of pteropod responses to environmental change is hindered by uncertainties surrounding their life cycles and population dynamics. In this study, we describe polar shelled pteropod diversity in the north-eastern Scotia Sea, inferring life history and population structures of the dominant pteropod species, Limacina rangii (formerly Limacina helicina antarctica) and Limacina retroversa. An annual timeseries of Limacina shell morphometrics was derived from individuals collected in a moored sediment trap at 400 m depth. We found that L. rangii and L. retroversa have contrasting life history strategies. L. rangii has a continuous spawning and recruitment period from November to March and can overwinter as juveniles and adults. L. retroversa has discrete spawning events from November to May, producing non–overlapping cohorts of juveniles and adults. Their development to the adult stage takes between two and five months, upon which they overwinter as adults. Our findings suggest different vulnerabilities of L. rangii and L. retroversa to a changing ocean. For example, since all life stages of L. rangii co-exist, vulnerability of one cohort is not detrimental to the stability of the overall population whereas, if one L. retroversa cohort fails to recruit, the entire population is threatened. Changes in pteropod populations could have cascading ramifications to Antarctic ecosystems and carbon cycling.